Técnicas para el estudio de las propiedades fisicoquímicas de los lipid droplets de Malassezia globosa (2020)
Malassezia globosa is a lipid-dependent yeast prevalent in the skin microbiota of several species, especially in areas with high sebum production. Despite being considered a commensal organism, it has been identified as the causative factor of the fungal infection pityriasis versicolor and has been associated with other skin conditions. To date, the pathogenicity mechanisms associated with this yeast remain unknown; however, the development of the disease is associated with changes in the abundance and lipid composition of the host's sebum. Therefore, it is important to study the organelles involved in lipid metabolism, known as lipid droplets (LDs). The physicochemical properties of LDs, such as stability, curvature, and electrostatic potential, to mention a few, could regulate the interaction with other organelles or influence their role under certain conditions. This monography explores a review of the techniques that could be applied to the study of the physicochemical properties of LDs...